Enhanced performance through a dual isolation seismic protection system. (31st August 2015) - Becker, Tracy C.; Ezazi, Ashkan
Summary: While base isolation successfully decreases the accelerations transmitted to a structure, a tradeoff is large unfavorable displacements in the isolation layer. This study investigates an innovative system, termed 'dual isolation', which applies two layers of isolation at the base and at mid‐story to resolve this issue. A linear analytical solution for the equation of motion of the proposed system is developed on the basis of linear isolation theory. This creates a foundation to assess the behavior of various types of seismic protection systems and to select the damping and mass ratio that optimizes the performance of the proposed method. Dynamic response of an example dual isolated system to selected suites of ground motions is then examined. In addition to decreasing the displacement of the first isolation layer, the dual isolation system can greatly decrease floor accelerations of the upper portion of the building, further protecting building components and enhancing the comfort and safety of residents. Copyright © 2015 John Wiley & Sons, Ltd.